The Influence of Leadership and Work Discipline on The Employees' Performance at PT Tri Centrum Fortuna - Maha Putra (Jurnal Ilmiah Poli Bisnis, 2021)
The research aims to determine the analysis of leadership and work discipline of employees' performance.The research used a quantitative method, conducted on 60 employees of PT Tri Centrum Fortuna, withsaturation or total sampling because the study participants were all employees; 60 people in total. The studyused primary data and secondary data. The data collection methods were observations, interviews,questionnaires, literature studies, and documentation studies. The data analysis used multiple linearregression to prove research hypotheses. The data was processed using SPSS 22 to meet the validity test,reliability, and classical assumption tests. The result shows that leadership positively and significantlyinfluences employee performance, with t calculate 4,498 > 2,003 and the significance level of 0.000 < 0.05.Work discipline has a positive and significant impact on employee performance, with t count 3,508 > 2,003and the significance level of 0.001 < 0.05. Leadership, work motivation, and work discipline have positiveinfluence simultaneously and significantly on employee performance; it is known that f count 29,319 > 2.77and significant level of 0.000 < 0,05.